2023
DOI: 10.1007/s12325-023-02505-1
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of REBYOTA™ (Fecal Microbiota, Live-jslm [FMBL]) Versus Standard of Care for the Prevention of Recurrent Clostridioides difficile Infection in the USA

Abstract: Introduction: Recurrent Clostridioides difficile infection (rCDI) is common and associated with considerable clinical and economic consequences. REBYOTA TM (fecal microbiota, livejslm [FMBL]) is a microbiota-based live biotherapeutic approved for the prevention of rCDI following antibiotic treatment for rCDI. We sought to evaluate cost-effectiveness of FMBL compared to standard of care (SOC) from a US third-party payer perspective among patients with one or more (C 1) recurrences. Methods: A Markov model with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Various studies have demonstrated the costeffectiveness and impact on quality of life of RBX2660 (REBYOTA). A study consisting of adult patients with ≥ 1 recurrence after a primary CDI and who had completed ≥ 1 round of antibiotics or had ≥ 2 severe CDI concluded that RBX2660 (REBYOTA) was cost-effective across all sensitivity analyses compared to the standard of care in preventing recurrent CDI [22]. Furthermore, other studies have demonstrated that treatment of recurrent CDI with RBX2660 (REBYOTA) improved patients' quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have demonstrated the costeffectiveness and impact on quality of life of RBX2660 (REBYOTA). A study consisting of adult patients with ≥ 1 recurrence after a primary CDI and who had completed ≥ 1 round of antibiotics or had ≥ 2 severe CDI concluded that RBX2660 (REBYOTA) was cost-effective across all sensitivity analyses compared to the standard of care in preventing recurrent CDI [22]. Furthermore, other studies have demonstrated that treatment of recurrent CDI with RBX2660 (REBYOTA) improved patients' quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…It must be administered as a rectal suspension and shipped frozen to pharmacies in a ready-to-administer enema bag. Furthermore, RBX2660 (REBYOTA) costs around $9500 per course in 2023, which may be a barrier, but economic analysis suggested that it is cost-effective compared to the standard of care [22]. RBX2660 (REBYOTA) significantly reduces recurrent CDI, but the cost may be a barrier to access and limit its use in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the Federal Drug Administration (FDA) recently approved the rectal administration of a probiotic suspension to prevent recurrent C. difficile infection. The technique is also more cost-effective when compared to traditional treatment (i.e., prolonged use of antibiotics, without subsequent administration of the probiotic suspension; Lodise et al, 2023;Walter and Shanahan, 2023).…”
Section: Introductionmentioning
confidence: 99%